Temporal and Spatial Changes of Vegetation Coverage in Duliu River Basin from 2000 to 2021 Based on MODIS Data - ZHAI Xiang; ZHAO Qingsong (Renmin Zhujiang)
Changes in vegetation coverage can reflect the improvement or degradation of the ecological environment,so as to help identify the evolution characteristics of the regional ecological environment.This paper takes the Duliu River Basin as the research area and calculates the vegetation coverage condition of the basin by using a pixel binary model based on MODIS-NDVI product data.The changing trend,fluctuations,and abnormal conditions of the vegetation coverage of the basin over the past 22 years are analyzed through the analyses of the trend,the anomalous percentage,and the coefficient of variation.The results indicate that ① the vegetation coverage in the Duliu River Basin is generally higher or high,with excellent performance and significant seasonal distribution characteristics;② the vegetation coverage is mainly increasing, and the similarity between summer and interannual changes is high,while the changing trend between spring and winter is similar;③ for the past 22 years,the annual vegetation coverage of the basin has mostly been in a normal state,with a relatively stable proportion in annual data.There are more abnormal states in spring and winter.The abnormal changes in vegetation coverage in the same season of different years are more significant compared with the annual data of different years;④ from 2000 to 2021,the overall vegetation coverage shows a stable state.However,the vegetation coverage in winter and spring is relatively unstable,and the fluctuation in winter and spring is more significant than that in summer and autumn.The interannual and summer distribution patterns are relatively consistent in terms of spatiotemporal changes.